Peran Operator Bogor Traffic Info Dalam Mempercepat Penanganan Laka Lantas - Dwi Angella (Police Studies Review, 2020)
Traffic accidents continue to increase every year,which results in many material losses experienced by the community. The number of traffic accidents recorded in Bogor Kota’s jurisdiction also has a slightly high number. The Traffic Unit plays a very important role in overcoming problems on the road. Polri members can urge people who already know about the Bogor Traffic Info (BTI) program created by members of the national police to inform or disseminate the program to the public. The purpose of this study was to determine the role of activities and methods carried out by BTI in handling accidents as well as knowing the factors the influence in the implementation of traffic accident handling in Bogor City Police. This type of research is a descriptive qualitative research.The location of this research is in Bogor City Polresta. Dara were analyzed by data reduction, data presentation and verification. The results of this study indicate that the method used to accelerate the handling of traffic accident then is by means of the community/police officers who are closest to report the traffic accident then through the BTI application that has been downloaded. The factors that suppirts and that is the ease of communication and cooperation with members of the traffic accident and the community,the police with the community who are proactive in communicating,support from elemnts of leadership in the police station. As of quantity of members and the quality of the personnel of the unit, which has been improved, than there is no budget,supporting infrastructure , and public knowledge that does not understand this application, and basic guidelines that are not clear about this application.